Tau in MAPK Activation - Leugers, Chad J.; Koh, Ju Yong; Hong, Willis; Lee, Gloria (Frontiers in Neurology, 2013)
The nature of “toxic” tau in Alzheimer’s disease (AD) has been unclear. During pathogenesis, the importance of tau oligomerization vs. tau phosphorylation is controversial and the investigation of both remains critical toward defining the “toxicity” of tau. The phosphorylation of tau on serines and/or threonines occurs early in the disease course and altering phosphorylation has been shown to disrupt neuropathogenesis. We have recently reported that in PC12-derived cells, tau had a role in signal transduction processes activated by NGF. By depleting tau, NGF-induced MAPK activation was attenuated and by restoring tau, MAPK activation was restored. Furthermore, the phosphorylation of tau on Thr231 was required for tau to potentiate MAPK activation. Here we report the effects of additional disease-related tau phosphorylation sites and tau isoform on the ability of tau to potentiate MAPK activation. Our findings, which tested three other sites of phosphorylation, showed that phosphorylation at these other sites mainly lessened MAPK activation; none potentiated MAPK activation. In comparing 0N3R tau to the other five brain tau isoforms, most showed a trend toward less MAPK activation, with only 2N4R tau showing significantly less activation. Since MAPK activation has been reported in AD brain and is characteristic of cell proliferation mechanisms, tau phosphorylation that promotes MAPK activation could promote cell cycle activation mechanisms. In neurons, the activation of the cell cycle leads to cell death, suggesting that abnormally phosphorylated tau can be a toxic species. The relationship between tau oligomerization and its ability to potentiate MAPK activation needs to be determined.